The Relationship of Literature Culture And Student's Learning Motivation with School Library Readiness in Sma Negeri 1 East Suwawa - Asni Ilham; Nina Lamatenggo; Hamzah Uno; Hadi Widodo (Green Publisher Indonesia, 2022)
The results showed that: (1) The relationship between literacy culture and school library readiness at SMA Negeri 1 Suwawa Timur. From the results of the research above, it is known that the test is carried out by comparing the alpha value with a significant value (0.006) > (0.05), then H 0 is rejected and H 1 is accepted. That is, partially there is a relationship between literacy culture with school library readiness. It can be concluded that literacy culture has a relationship with the readiness of school libraries at SMA Negeri 1 Suwawa Timur. (2) The relationship between students' learning motivation and the readiness of the school library at SMA Negeri 1 Suwawa Timur The test is done by comparing the alpha value with a significant value (0.000) > (0.05) then H 0 is rejected and H 1 is accepted. That is, partially there is a relationship between student learning motivation and school library readiness. It can be concluded that partially there is a relationship between school library readiness and student learning motivation at SMA Negeri 1 Suwawa Timur. (3) The Relationship between Literacy Culture, learning motivation and school library readiness for students at SMA Negeri 1 Suwawa Timur. count (496.29) > F table value (2.70) with a significant value (0.000) > (0.05) then H 0 is rejected and H 1 is accepted. That is, there is a relationship between Literacy culture of learning motivation with school library readiness can be concluded that simultaneously the literacy culture of student learning motivation with school library readiness at SMA Negeri 1 Suwawa Timur.